Analysis of biomedical waste management case laws: an Indian perspective vs. European guidelines - Dr.Akshay Kumar,; Dr.Somu G, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The handling, treatment, and disposal of biological waste produced by healthcare facilities are regulated by a distinct set of laws and regulations aimed at ensuring safety and efficacy. Conducting a systematic review of case laws for biomedical waste management is essential for understanding the Legal Precedents. Methods: Systematic review was conducted using PRISMA guidelines for the case laws related to biomedical waste management for non-compliance with existing rules using the legal search engine www.indiankanoon.org and summarized using www.casemine.com, the findings were provided in a summary of table for each outcome and synthesised qualitatively. A literature review was conducted usingexisting articles on Biomedical Waste Management in European countries. Results: Atotal of 604 records were retrieved, of which 556 were selected from 2012 to 2024. Among these, 26 relevant case records were selected for full screening. The Results are summarized in tabular form and elaborated in four columns: case laws, facts, issues and decision. Conclusion: This study shows the need for periodic surveillance of institutions handling biomedical waste for compliance in the interest of community well-being. In European countries it can be observed that guidelines are strictly followed and there are minimal requirement of intervention by law.